Demographic Characteristics of Children Diagnosed with Bacterial Tracheitis. (December 2021) - Barengo, Jenna H.; Redmann, Andrew J.; Kennedy, Patrick; Rutter, Michael J.; Smith, Matthew M.
Objectives: Examine the presentation and clinical course of patients with bacterial tracheitis (BT). Identify if socioeconomic differences exist among children who present with BT. Methods: This was a retrospective case series from a tertiary care pediatric medical center. The study group included patients less than 18 years old who were diagnosed with BT from January 2011 to March 2019. Patients with a tracheostomy and those who developed BT after prolonged hospitalization were excluded. Patient demographics were compared with the demographics of the counties surrounding the hospital. Results: 33 patients with BT met inclusion criteria. The most common presenting symptoms were difficulty breathing, stridor, and sore throat (81.8% each), followed by cough (78.8%). Median length of stay was 3 days [interquartile range (IQR):2-4]. 19 patients (57.5%) were admitted to the intensive care unit. Intubation was required for 13 patients (39.4%), for a median length of 2 days [IQR:2-2]. Methicillin sensitive staphylococcus aureus was the most common bacterial etiology (33%). Mean presenting age was 8.58 years [95% confidence interval:7.3-9.9] and 14 patients were female (42.4%). 31 patients were white (93.9%), 1 was black (3%), and 1 was Hispanic (3%). BT patients were more likely to have private insurance compared to comparison (81.8% vs 63.4%, P  < .001). Conclusion: Children who presented with BT were more likely to be privately insured than a comparison population.